Better visual outcome associated with early vitrectomy in the management of endophthalmitis. Issue 8 (12th March 2021) - Welch, Sarah; Bhikoo, Riyaz; Wang, Nancy; Siemerink, Martin J; Shew, William; Polkinghorne, Philip J; Niederer, Rachael L
Abstract : Aims: To examine the role of early vitrectomy in the management of endophthalmitis from all causes. Methods: Retrospective study of 290 consecutive subjects diagnosed with endophthalmitis at Auckland District Health Board between 1 January 2006 and 31 July 2019. Main outcome measure was visual acuity at 9-month follow-up and proportion of subjects with severe vision loss (≤20/200). Results: Median age at presentation was 70.4 years and 151 subjects (52.1%) were women. Cataract surgery was the most common cause of endophthalmitis in 92 subjects (31.7%) followed by intravitreal injection in 57 (19.7%), endogenous endophthalmitis in 48 subjects (16.6%), non-surgical trauma in 42 subjects (14.5%), glaucoma surgery in 24 subjects (8.3%), vitrectomy in 22 subjects (7.6%) and corneal in 5 subjects (1.7%). Culture was positive in 136 (46.9%) with gram-positive organisms most common (76.5%). Early vitrectomy was performed in 82 subjects (28.3%). Median visual acuity at 9 months was 20/100 (IQR 20/30 to light perception), and severe vision loss occurred in 100 (43.5%). Retinal detachment occurred in 35 eyes (12.1%) and 26 eyes were enucleated. On multivariate analysis, younger age, poor presenting visual acuity and culture-positive endophthalmitis were associated with worse outcomes, and early vitrectomy was associated with better outcomes. Conclusions: Early vitrectomy (within 24 hours) is associated with better visual outcomes at 9 months, while younger age, poor presenting visual acuity and culture-positive endophthalmitis are associated with poorer visual acuity outcomes.